2006
DOI: 10.1111/j.1742-4658.2006.05156.x
|View full text |Cite
|
Sign up to set email alerts
|

The potyviral virus genome‐linked protein VPg forms a ternary complex with the eukaryotic initiation factors eIF4E and eIF4G and reduces eIF4E affinity for a mRNA cap analogue

Abstract: The virus protein linked to the genome (VPg) of plant potyviruses is a 25‐kDa protein covalently attached to the genomic RNA 5′ end. It was previously reported that VPg binds specifically to eIF4E, the mRNAcap‐binding protein of the eukaryotic translation initiation complex. We performed a spectroscopic study of the interactions between lettuce eIF4E and VPg from lettuce mosaic virus (LMV). The cap analogue m7GDP and VPg bind to eIF4E at two distinct sites with similar affinity (Kd = 0.3 µm). A deeper examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 38 publications
2
90
0
1
Order By: Relevance
“…We were interested in determining how eIF4G altered these kinetic constants in light of reports that eIF4G peptides containing the eIF4E-binding domain increased cap affinity (15,(17)(18)(19)(20)(21)(22). Previous studies with mammalian eIF4E utilized eIF4G-related peptides ranging from 12 to 20 aa, which bound eIF4E with K d Х 30 nM (6,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were interested in determining how eIF4G altered these kinetic constants in light of reports that eIF4G peptides containing the eIF4E-binding domain increased cap affinity (15,(17)(18)(19)(20)(21)(22). Previous studies with mammalian eIF4E utilized eIF4G-related peptides ranging from 12 to 20 aa, which bound eIF4E with K d Х 30 nM (6,14).…”
Section: Discussionmentioning
confidence: 99%
“…The affinity of full-length recombinant human eIF4E for a fluorescently labeled cap analog, Ant-m 7 GTP, was 2-fold higher in the presence of a 20-aa peptide containing the eIF4E-binding sequence of human eIF4G (19). An 11-aa peptide containing the eIF4E-recognition motif of Arabidopsis thaliana eIF4G increased the affinity of full-length recombinant lettuce eIF4E to m 7 GDP ϳ2-fold (20). Qualitative m 7 GTP-Sepharose pulldown and gel-shift experiments were also interpreted to mean that the affinity of full-length recombinant yeast eIF4E to m 7 GTP or a short capped RNA is increased in the presence of full-length recombinant yeast eIF4G-1 or eIF4G(393-490) (15,21,22).…”
Section: ؊1 Smentioning
confidence: 99%
“…It has been noted that the eIF4E proteins encoded by the pvr1 allele from pepper and the sbm1 allele from pea, which both contain the G107R substitution, show reduced cap binding (Gao et al, 2004;Kang et al, 2005a). Recent studies have suggested that the mRNA cap structure and potyvirus VPg at least partially share the protein binding pocket structure of the eIF4E protein or its isoform eIF(iso)4E (Michon et al, 2006;Miyoshi et al, 2006).…”
Section: The Vpg Binding and Cap Binding Abilities Of Eif4e Are Strucmentioning
confidence: 99%
“…However, it has been shown that the viral protein VPg can interfere with cap binding ability of eIF4E or its isoform eIF(iso)4E, which likely is responsible for the interruption of the formation of the translation initiation complex . Additionally, a number of recent studies have demonstrated that eIF4G, which functions as an adapter connecting the translation initiation complex with the 40S ribosomal subunit, and the leader sequence of the Tobacco etch virus (TEV) RNA genome are also involved in the formation of the complex including eIF4E and VPg Michon et al, 2006;Ray et al, 2006;Nicaise et al, 2007), which further demonstrates the involvement of the host translation initiation machinery in the initial steps of viral infection. Interestingly, the involvement of host translation initiation machinery during the viral infection process is not unique to the plant/potyvirus pathosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting eIF4E-m 7 G cap-binding activity in a phase II trial in leukemia patients led to clinical benefit (7), which further underscores the importance of understanding the regulation of this eIF4E activity at the molecular level. eIF4E is regulated by many key effectors that can be grouped into three classes: (i) those containing a conserved eIF4E binding motif such as eIF4G; (ii) those containing a Really Interesting New Gene (RING) domain, e.g., arenaviral Z proteins; (iii) others, such as the viral protein linked to the genome (VPg) (8).…”
mentioning
confidence: 99%